Parts in Play: The Rosalynde Osborne Stearn Collection at McGill University - Flegel, Loretta (Université Concordia, 2003)
Keywords: Théâtre; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

L’Office provincial des recherches scientifiques et le développement de la science au Québec, 1937-1960 - Almeida, Mike (Revue d'histoire de l'Amérique française, 2002)
Number: 2
Keywords: Université McGill; Université de Montréal

From Osler’s Library to the Osler Library of the History of Medicine, McGill University, Montreal: An Overview - Lyons, Christopher (Canadian Bulletin of Medical History, 2007)
Number: 1
Keywords: Bibliothèque Osler; Médecine; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
issued: 2002-08/2002-11
Keywords: Criminalité; Médecine; Université McGill; Étudiants

The Club Art Collection / La Collection d'oeuvres d'art du Club - Murphy, Sean B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Peinture; University Club; Université McGill

The Club and the Two World Wars / Le Club et les deux guerres mondiales - Claxton, John B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Guerre; Poésie; University Club; Université McGill

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: McEachran; Duncan McNab; Université McGill; École de médecine vétérinaire

J.W. McConnell: Financier, Philanthropist, Patriot - Fong, William Jesse (McGill-Queen's University Press, 2008)
Keywords: Clubs; Hommes d'affaires; McConnell; John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Forging the Corporate Identity with Art: Four Montreal Corporations: Alcan Aluminium Limited, Martineau Walker, Banque Nationale du Canada, Loto-Quebec with a focus on Alcan - Meade, JoAnn (Université McGill, 2000)

La critique littéraire au Québec en 1950: analyse de La Presse, Le Quartier latin, Le Devoir et Lectures - Deslierres, Deborah (Université McGill, 2005)
Keywords: Devoir (Le); Presse (La); Quartier latin (Le)

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Le personnage de Julie Bruneau dans la correspondance de Papineau - Arbach, Marla (Université McGill, 2001)
Keywords: Papineau; Louis-Joseph

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Salsa and its Transnational Moves: The Commodification of Latin Dance in Montreal - Pietrobruno, Sheenagh (Université McGill, 2001)
Keywords: Danse

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

Not a Place, but a Culture: The Cultivation of Iranian Subjectivity in Montreal - Hashemzadeh, Kianoosh (Université McGill, 2009)
Keywords: Iraniens

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

The Conservation of a Gender Fantasy: Women and Top 40 Radio in Montreal - Maki, Christine (Université McGill, 2008)
Keywords: Femmes; Radio

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

How Does what's Bred in the Bone Come Out in the Flesh? Devora Neumark's Interventions and the Concept of Flesh - Kiriloff, Vera (Université McGill, 2005)

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

Art, identité et Expo 67. L'expression du nationalisme dans les œuvres des artistes québécois du Pavillon de La Jeunesse à l'Exposition universelle de Montréal - Hellman, Michel (Université McGill, 2005)
Keywords: Expositions; Nationalisme

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith; Donald